Physio-Biochemical Indexes as Indicators of Cadmium Tolerance in Brassica napus L. Cultivars - Yu Qiu; Shuhe Wei; Jie Zhan; Brett H. Robinson; Lidia Skuza; Jianming Xue; Huiping Dai; Li Zhan; Ziyang Tang (Agriculture)
Cadmium (Cd) is a non-essential heavy metal and a pervasive pollutant in agricultural soils. Despite numerous studies investigating Cd accumulation and tolerance in plants, there is a lack of systematic analysis of how various physio-biochemical indexes respond to Cd toxicity, particularly their indicative role in plant tolerance mechanisms. A pot experiment was conducted in greenhouse to assess the differences in Cd accumulation and tolerance among three Brassica napus L. cultivars (‘Hanyou 2’, ‘Hanyou 3’, and ‘Hanyou 16’) under the treatments of CK (0.18 mg kg−1 in soil), T1 (2.18 mg kg−1 in soil), T2 (4.18 mg kg−1 in soil), and T3 (8.18 mg kg−1 in soil). All three cultivars exhibited high tolerance indexes (TIs) and strong Cd tolerance when exposed to a Cd concentration of 2.18 mg kg−1 in soil (T1). There were significant positive correlations between TI and chlorophyll a (Chla), chlorophyll b (Chlb), carotenoids (Car), net photosynthetic rate (Pn), transpiration rate (Tr), and activities of antioxidant enzymes and non-enzymatic antioxidants such as superoxide dismutase (SOD), ascorbate peroxidase (APX), glutathione (GSH), and ascorbic acid (ASA), while negatively correlating with intercellular CO2 concentration (Ci) and malondialdehyde (MDA) content. These findings underscore the significant indicative role of these physio-biochemical indexes in elucidating Cd tolerance mechanisms in B. napus and may be used in breeding programs to develop cultivars with a high Cd-tolerance but low Cd uptake profile. However, this was a pot experiment only. Field experiments might be more useful in the future.